2022
DOI: 10.1155/2022/4565968
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stress State Assessment Method for College Students Based on EEG

Abstract: Stress is an unavoidable problem for today’s college students. Stress can arouse strong personal emotional and behavioral responses. Compared with other groups of the same age, college students have a special way of life and living environment. They have complex interpersonal relationships and relatively weak social support systems. At the same time, they also face fierce competition in both academic and employment. However, they lack the skills to deal with the crisis and are reluctant to ask others for help,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…New developments have not only occurred in hardware, but new software and processing techniques have also emerged. In 2022 [ 48 ], a study found better classification results from EEG data as a predictor of student stress through the use of an improved extreme learning machine model. A useful approach for EEG processing uses traditional SVMs whose features were extracted through empirical mode decomposition to obtain a higher classification accuracy in predicting student interest [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New developments have not only occurred in hardware, but new software and processing techniques have also emerged. In 2022 [ 48 ], a study found better classification results from EEG data as a predictor of student stress through the use of an improved extreme learning machine model. A useful approach for EEG processing uses traditional SVMs whose features were extracted through empirical mode decomposition to obtain a higher classification accuracy in predicting student interest [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, an increase in mental fatigue was discovered to increase on 8 h school days (or longer), and it was identified as a factor of high concern in high-school education [ 64 ]. Some studies also developed algorithms for emotion recognition in teachers [ 46 ] and to evaluate psychological stress in students [ 48 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the increase of mental fatigue was discovered to increase on 8-hour school days (or longer), and it was identified as a factor of high concern in high school education [66]. Some studies also developed algorithms for emotion recognition in teachers [46], and to evaluate psychological stress in students [48,70].…”
Section: Discussionmentioning
confidence: 99%
“…New developments have not only occurred with hardware, but new software and processing techniques have emerged. In 2022 [48], a study found better classification results from EEG data as a predictor of student stress through the use of an improved Extreme Learning Machine model. A useful approach for EEG processing uses traditional SVMs whose features were extracted through Empirical Mode Decomposition to obtain a higher classification accuracy to predict student interest [100].…”
Section: Evolution Of Wbt In Educationmentioning
confidence: 99%

Wearable Biosensor Technology in Education: A Systematic Review

Hernández-Mustieles,
Lima-Carmona,
Pacheco-Ramírez
et al. 2024
Preprint
“…has good classification performance in this study and is able to gauge the stress levels of kids with accuracy. The growth of students' mental health has a strong foundation thanks to the precise measurement of stress, which also has important practical ramifications [21]. This research explores the concept of the intervention effect of physical activity on college students using an integrated evaluation-based algorithm.…”
Section: Introductionmentioning
confidence: 99%